A Comparative Study of Asymptomatic Malaria in a Forest Rural and Depleted Forest Urban Setting during a Low Malaria Transmission and COVID-19 Pandemic Period. (15th October 2022) - Mbah, Clarisse E.; Ambe, Lum A.; Ngwewondo, Adela; Kidzeru, Elvis B.; Akwah, Lilian; Mountchissi, Celestin; Mansour, Mohamadou; Sahfe, Edward N.; Kamgang, Rene´; Nkengazong, Lucia
Abstract : The global malaria morbidity and mortality witnessed an increase from 2019 to 2020 partly due to disruptions in control programs' activities imposed by the COVID-19 pandemic. Therefore, there is still a significant burden of malaria in Cameroon which needs attention from all fronts to attain elimination goals. It is normally expected that a typical forest ecology that has undergone urbanization and subjected to high rates of ecological instabilities should also have a shift from characteristic perennial malaria transmission and a shift in the type of malaria endemicity plaguing such distorted forest ecology. In this observational comparative study, we randomly enrolled participants from rural and urban settings of a forest zone during a low malaria transmission period, which coincided with the onset of COVID-19 pandemic. An optimized structured questionnaire was employed, to collect socio-demographic data and associated risk factors. The CareStart™ Malaria HRP2 antigen test was performed on participants from both settings to determine the prevalence of community asymptomatic malaria. Of 307 participants, 188 (61.0%) were from the rural, while 119 (38.8%) from the urban community. The overall prevalence of asymptomatic malaria (27.0%) detected Plasmodium falciparum antigen in 83 participants. The urban community's prevalence was 4.2% (5 positives) while the rural community's was 41.5% (78 positives). In simple logistic regression models, rural forest community and farm around the house were statistically significant predictors of testing positive (coefficient 2.8, 95% CI 1.8-3.7, p value<0.001) and (coefficient 3.1, 95% CI 1.1-5.1, p value =0.003), respectively. In the multivariate model, the strongest predictor of testing positive was living in a rural community, with p < 0.001 and odds ratio of 10.9 (95% CI, 3.8-31.8). These results indicate that during a low transmission period, the prevalence of asymptomatic malaria differs between depleted urban and rural forested settings, suggesting a need for strategic target intervention for the control of asymptomatic malaria.